Colonial Tube-Dwelling Ciliates Influence Methane Cycling and Microbial Diversity within Methane Seep Ecosystems - Pasulka, Alexis L.; Goffredi, Shana K.; Tavormina, Patricia L.; Dawson, Katherine S.; Levin, Lisa A.; Rouse, Greg W.; Orphan, Victoria J. (Frontiers in Marine Science, 2017)
In a variety of marine ecosystems, microbial eukaryotes play important ecological roles; however, our knowledge of their importance in deep-sea methane seep ecosystems is limited. Microbial eukaryotes have the potential to influence microbial community composition and diversity by creating habitat heterogeneity, and may contribute to carbon cycling through grazing or symbiotic associations with microorganisms. In this study, we characterized the distribution, substrate variability and ecology of a particular group of microbial eukaryotes, known as folliculinid ciliates, at methane seeps along the eastern Pacific margin. Folliculinid ciliates were recently recognized as an abundant and ecologically important component of hydrothermal vent ecosystems, but their ecology in methane seeps has not been examined. Folliculinid ciliates inhabited methane seeps from Costa Rica to Oregon, suggesting a broad distribution in the eastern Pacific. Using phylogenetic analyses of the 18S rRNA gene, two different species of folliculinid were identified. Folliculinids occupied a range of physical substrates, including authigenic carbonate rocks, shells of dead vesicomyid clams, polychaete tubes and gastropod shells. Molecular analysis of folliculinid associated microorganisms (16S rRNA and particulate methane monooxygenase) revealed that these ciliates not only influence overall microbial diversity, but also and have a specific relationship with bacteria in the ‘Deep sea-2’ methanotroph clade. Natural δ13C isotope signatures of folliculinids (-35‰) and their 13C-enrichment patterns in shipboard 13CH4 stable isotope-probing experiments indicated these ciliates and their associated microbes are involved in cycling methane-derived carbon. Folliculinids were significantly enriched in 13C after the addition of 13CH4 over short-term (3-8 day) incubations. Together, these results suggest that folliculinid ciliates represent a previously overlooked contributor to the ecology and biogeochemical cycling of deep-sea methane seep ecosystems.